THE URGENCY OF TEACHING PRACTICES ON PROSPECTIVE TEACHERS’ TEACHING ABILITY - Rahmi Rahmawati; Eva Latipah; Ghulam Murtadlo (JURNAL EDUSCIENCE, 2023)
Education is a kit for a person to free from the shackles of ignorance, poverty, and underdevelopment. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students. Teaching practice is an effort to demonstrate the competence of prospective teachers in planning, carrying out learning and assessing the effectiveness of learning. This study aims to determine the urgency of teaching practice on the teaching abilities of prospective teachers. The research method is using literature study. The results of the study show that teaching practice is one of the most important, because practice means conducting real experiments and during the experiment a practitioner pays attention to the ongoing process until finally knowing something is lacking and then trying to fix it. Teaching practice is carried out as an implementation of improving the teaching and learning process in the classroom. Teaching practice is something urgent that must be carried out by every student teacher candidate, because it trains them so that they have the ability to demonstrate performance in real situations in learning activities in educational institutions in the future.Keywords: The Urgency of Teaching Practice and Teaching SkillsAbstrakPendidikan menjadi wahana agar seseorang terbebas dari belenggu kebodohan, kemiskinan, maupun keterbelakangan. Guru adalah pendidik professional dengan tugas utama mendidik, mengajar, membimbing, mengarahkan, melatih, menilai, dan mengevaluasi peserta didik. Praktik mengajar merupakan suatu upaya yang menunjukkan kompetensi mahasiswa calon guru dalam merencanakan, melaksanakan pembelajaran hingga menilai efektivitas pembelajaran. Penelitian ini bertujuan untuk mengetahui urgensi praktik mengajar terhadap kemampuan mengajar mahasiswa calon guru. Metode penelitiannya yaitu menggunakan studi pustaka. Hasil penelitian menunjukkan bahwa praktik mengajar menjadi salah satu yang terpenting, karena praktik berarti melakukan percobaan yang bersifat nyata dan selama percobaan tersebut seorang praktikan memperhatikan proses yang berlangsung hingga akhirnya mengetahui kekurangan suatu hal kemudian berusaha memperbaikinya. Praktik mengajar dilakukan sebagai implementasi perbaikan proses belajar mengajar di kelas. Praktik mengajar merupakan sesuatu yang urgent yang harus dilaksanakan oleh setiap mahasiswa calon guru, karena hal tersebut melatihnya agar memiliki kemampuan memperagakan kinerja dalam situasi nyata dalam kegiatan pembelajaran di lembaga pendidikan kelak.Kata Kunci: Urgensi Praktek Mengajar dan Keterampilan Mengajar